Aplikasi Akademik Smk Sinar Permata Bangsa Sragen Berbasis Website - Marwiyanto, Yuwan Agus, Umi Fadlillah, ST. MEng (2015)
Increasing of information technology in this era has already finished developing very fast, many facilities has begin that saved to fill all they need, one of them is website which is used in the education world that has a function as data process (data basic) web basic. Sinar Permata Bangsa Sragen vocational high school is a new builded school, as far as needs academic application to ease the process which is correlated with the school academic. Creating this academic application begins with spot interview of the teacher and the students in Sinar Permata Bangsa vocational high school, then continued with the necessaries analysis of system and design system. This academic application is designed using PHP programme language and MySQL as database. The research produce an academic application based website that used to make easier the process of data related to academic especially for the teacher and the students in Sinar Permata Bangsa Sragen vocational high school. The teacher and the students can see the schedule and the score that can be spoting downloaded.